Kompetensi Multikultural Konselor pada Kebudayaan Suku Dayak Kalimantan Tengah - Riswanto, Dody; Mappiare-AT, Andi; Irtadji, Mohammad (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
The aim of this research is to comprehend multicultural competency of counselor in Dayak tribe in the Middle Kalimantan with etnography type. The data analysis that used is data and analysis triangulation towards culture theme. Accordingly, the culture values of Dayak ethnic that reflects on Huma Betang filosophy consists of four main values, they are togetherness, honesty, equality and tolerance. They are aimed to actualize society life of the Middle Kalimantan that full of peace, safety and harmony. Counselor absorps the culture values to actualize multikultural competency on counselor.